The use of ambon banana (Musa paradisiaca var. sapientum) stems flour in grouper (Epinephelus lanceolatus ♂× Epinephelus fuscoguttatus ♀) floating net cage nursery - Dinamella Wahjuningrum; Diah Ayu Lestari; Aldy Mulyadin; Irzal Effendi (Jurnal Akuakultur Indonesia)
The study aimed to test the effectiveness of ambon banana stems flour through feeding on the health status and performance of the groupers reared in the sea floating net cages. The groupers (8.27 ± 0.20 cm length and 11.69 ± 0.50 g weight) were reared in 1 m × 1 m × 1.5 m floating net cages with a stocking density of 112 fish /m3 for 42 days. The feed was commercial feed with 46% and 48% protein, which was added with 30 g/kg of ambon banana stems flour with a coating method. This study consists of three treatments and three replications, i.e. feeding at the beginning of reared for 7 days (A), 14 days (B), and feeding without ambon banana stems flour (control). The observed parameters were production performance, morphometric, hematological test, and water quality. The results showed that the production performance between treatments was not significantly different (P>0.05). Based on the morphometric test the total length for treatment A increased significantly (P <0.05) compared to the control and B. On the 14th day of the hematological test, it was known that the highest total erythrocyte, hemoglobin, hematocrit, and total leukocyte was found in treatment B, however, the differential leukocyte did not differ significantly (P>0.05). The addition of Ambon banana stems flour in feed in the first 14 days (B) can improve health status but has not been able to increase production performance and morphometric grouper.